2018
DOI: 10.1002/ejhf.1305
|View full text |Cite
|
Sign up to set email alerts
|

Screening, diagnosis and treatment of iron deficiency in chronic heart failure: putting the 2016 European Society of Cardiology heart failure guidelines into clinical practice

Abstract: Iron deficiency is common in patients with chronic heart failure (CHF) and is associated with reduced exercise performance, impaired health‐related quality of life and an increased risk of mortality, irrespective of whether or not anaemia is present. Iron deficiency is a serious but treatable condition. Several randomized controlled clinical trials have demonstrated the ability of intravenous (IV) iron, primarily IV ferric carboxymaltose (FCM), to correct iron deficiency in patients with heart failure with red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
99
0
12

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 40 publications
0
99
0
12
Order By: Relevance
“…36 Awareness of the benefits of treating iron deficiency and iron deficiency anaemia with high-dose intravenous iron across various medical and surgical conditions is steadily increasing, with improvements reported in patient quality of life and disease outcomes, and reductions in morbidity. [37][38][39] However, the finding in this study of persistent moderate to severe hypophosphatemia beyond 6 weeks after intravenous iron treatment with ferric carboxymaltose is a clinical concern that requires further investigation. In general, monitoring phosphate levels for longer than 6 weeks after administration of intravenous iron may be unnecessary.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…36 Awareness of the benefits of treating iron deficiency and iron deficiency anaemia with high-dose intravenous iron across various medical and surgical conditions is steadily increasing, with improvements reported in patient quality of life and disease outcomes, and reductions in morbidity. [37][38][39] However, the finding in this study of persistent moderate to severe hypophosphatemia beyond 6 weeks after intravenous iron treatment with ferric carboxymaltose is a clinical concern that requires further investigation. In general, monitoring phosphate levels for longer than 6 weeks after administration of intravenous iron may be unnecessary.…”
Section: Discussionmentioning
confidence: 70%
“…Anaemia is one of the most common extra‐intestinal manifestations in IBD, and one of the most common health‐related problems world‐wide . Awareness of the benefits of treating iron deficiency and iron deficiency anaemia with high‐dose intravenous iron across various medical and surgical conditions is steadily increasing, with improvements reported in patient quality of life and disease outcomes, and reductions in morbidity . However, the finding in this study of persistent moderate to severe hypophosphatemia beyond 6 weeks after intravenous iron treatment with ferric carboxymaltose is a clinical concern that requires further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…[58][59][60] Ferric carboxymaltose improves functional capacity, symptoms, and quality of life of HF patients with iron deficiency. 61,62 A meta-analysis of data from the four major randomized controlled trials conducted, to date, demonstrated also a reduction in recurrent CV hospitalizations ( Figure 2). 63 Ongoing trials are aimed at showing the impact of iron therapy on outcomes, including mortality.…”
Section: Treatment Of Iron Deficiencymentioning
confidence: 98%
“…101,102,188,189 The contribution of comorbidities to patients' outcomes may be similar in patients with HFrEF, compared with those with HFpEF, 189 or be larger in those with HFpEF according to other analyses. 60,61,63,201 They were all shown to have a major impact on clinical presentation, response to treatment and outcomes. 60,61,63,201 They were all shown to have a major impact on clinical presentation, response to treatment and outcomes.…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation